2012
DOI: 10.4025/actascianimsci.v34i3.12735
|View full text |Cite
|
Sign up to set email alerts
|

Associação de carboidrase e fitase em dietas valorizadas para poedeiras semipesadas

Abstract: RESUMO. O objetivo do estudo foi avaliar o efeito da associação de carboidrases e fitase em dietas de poedeiras. Foram utilizadas 300 poedeiras Isa Brown com 26 semanas, submetidas aos tratamentos: Controle Positivo: sem enzimas e valorização dos nutrientes; T2: valorização em 1,5 e 6% a EMA (kcal kg-1), do milho e o farelo de soja, respectivamente, e redução nos níveis nutricionais conforme a matriz nutricional para a fitase; T3: valorização da EMA do milho e o farelo de soja (idem T2) e redução nos níveis de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…Vieira Filho et al (2015) observed an increase in the laying rate by adding 500 g ton-1 of protease (100 Ug-1) to diets of Isa Brown commercial layers at 44 weeks old with reduced nutritional levels. Similarly, Silva et al (2012) observed a similar effect, reporting that birds fed diets with nutritional reduction and without supplementation of enzymes presented worse rates of feed conversion, confirming the positive effect of the inclusion of enzymes in diets of laying hens. From this study, it can be concluded that the inclusion of protease B improved the digestibility of nutrients and, consequently, increased the availability of amino acids for absorption, thus improving protein synthesis.…”
Section: Protease Supplementation In the Diet Of Light Laying Henssupporting
confidence: 55%
“…Vieira Filho et al (2015) observed an increase in the laying rate by adding 500 g ton-1 of protease (100 Ug-1) to diets of Isa Brown commercial layers at 44 weeks old with reduced nutritional levels. Similarly, Silva et al (2012) observed a similar effect, reporting that birds fed diets with nutritional reduction and without supplementation of enzymes presented worse rates of feed conversion, confirming the positive effect of the inclusion of enzymes in diets of laying hens. From this study, it can be concluded that the inclusion of protease B improved the digestibility of nutrients and, consequently, increased the availability of amino acids for absorption, thus improving protein synthesis.…”
Section: Protease Supplementation In the Diet Of Light Laying Henssupporting
confidence: 55%
“…These data agree with those of Ribeiro et al (2015), who found no differences in the specific weight of eggshells, an element corresponding to the specific gravity evaluated in the present study. Lima et al (2011), who worked with Japanese quail, and Silva et al (2012), who worked with semiheavy laying hens, also found no differences in the evaluation of shell weight, shell thickness or egg specific gravity when hens were supplemented with various levels of phytase. The composition of the eggshell is mostly calcium carbonate; therefore, the mineral that exerts the greatest influence on its composition and quality is calcium.…”
Section: Resultsmentioning
confidence: 95%
“…3 P AD = 35.38915 + 0.06966X -0.00039189X 2 (R 2 = 0.56). Silva et al (2012) studied the association of 100 mg.kg -1 carbohydrase and 30 mg.kg -1 phytase in feed for commercial brown-egg layers using a diet without enzymes and test diets enriched with energy and nutrients according to the nutrient matrix and of enzymes did not find a significant effect of treatments on the performance of birds. The authors attributed this effect to the good metabolic utilization of the diets containing enzyme supplementation.…”
Section: Discussionmentioning
confidence: 99%